Keanekaragaman jenis hasil hutan bukan kayu di Plot Permanen di Sungai Tapah, Jambi - Y. Purwanto; Eko Baroto Walujo; J. J. Afriastini (The Ethnobiological Society of Indonesia, 2005)
Study on diversity of non timber forest products (NTFPs) in conservation area of PT Wirakarya Sakti represent the part of project research on